In situ statistical observations of Pc1 pearl pulsations and unstructured EMIC waves by the Van Allen Probes. Issue 1 (3rd January 2017) - Paulson, K. W.; Smith, C. W.; Lessard, M. R.; Torbert, R. B.; Kletzing, C. A.; Wygant, J. R.
Abstract: We present here the first in situ statistical survey of structured Pc1 pearl pulsations compared with unstructured electromagnetic ion cyclotron (EMIC) waves observed by the Van Allen Probes spacecraft. This data set was compiled from observations spanning 8 September 2012 through 31 August 2015 and comprises over 1630 h of total EMIC wave activity, of which 291 h exhibited pearl structure. Additionally, we have identified 29 wave events demonstrating periodically oscillating wave packets, mostly about the magnetic equator, indicated by the reversal of Poynting flux along the background magnetic field. We have found several stark differences between Pc1 pearl pulsations and unstructured EMIC waves. While unstructured EMIC waves demonstrate the predicted behavior of a higher occurrence across the dayside with enhanced wave power at dusk, pearl pulsations occur uniformly across magnetic local time, with a small enhancement in the late morning sector. Pearl pulsations were more often observed during magnetospherically quiet periods, particularly in the late recovery period of geomagnetic storms. The mean excitation frequency of pearl pulsations was observed to be independent of the local ion cyclotron frequency, and individual wave investigations indicate that the modulation period also remained constant for the duration of the event over a finite range in L . We examine three possible generation mechanisms—the bouncing wave packet model, modulation by ultralow‐frequency Pc4 and Pc5 waves, and the formation of an ion cyclotron resonator—but are unable to definitively confirm the validity of any one model. Key Points: First statistical distribution of Pc1 pearl pulsations made with in situ measurements Pearl pulsations seen at different spatial locations and during different storm phases than unstructured EMIC waves Constant excitation and modulation frequencies defy currently proposed generation mechanisms